Hepatoprotective effect by pretreatment with olprinone in a swine partial hepatectomy model. Issue 7 (26th May 2014) - Iguchi, Kohta; Hatano, Etsuro; Yamanaka, Kenya; Sato, Motohiko; Yamamoto, Gen; Kasai, Yosuke; Okamoto, Tatsuya; Okuno, Masayuki; Taura, Kojiro; Fukumoto, Kyoko; Ueno, Kazuyuki; Uemoto, Shinji
<x xml:space="preserve">Abstract</x> Excessive portal flow to a small remnant liver or small‐for‐size graft is a primary factor of small‐for‐size syndrome. We demonstrated that olprinone (OLP), a phosphodiesterase III inhibitor, had a hepatoprotective effect in a rat extended hepatectomy model and a small‐for‐size liver transplantation model through a modification of the portal venous pressure (PVP). To identify the appropriate dose and duration of treatment for clinical applications, we conducted experiments with a swine partial hepatectomy model. Twenty microminipigs were divided into 4 groups that received the following treatments: (A) saline (control group), (B) OLP at 0.3 μg/kg/minute (preoperative and postoperative administration), (C) OLP at 0.1 μg/kg/minute (preoperative administration), and (D) OLP at 0.3 μg/kg/minute (preoperative administration). The pigs underwent 70% partial hepatectomy. Hemodynamic changes, including changes in PVP, were examined. Liver biopsy was performed 1 and 3 hours after hepatectomy. Blood samples were collected until postoperative day 7 (POD7). In comparison with group A, PVP elevations, periportal edema, and sinusoidal hemorrhaging were attenuated after left Glisson's ligation in groups C and D. Pretreatment with OLP in groups C and D preserved the microstructure of sinusoids and improved the prothrombin activity 1 and 3 hours after hepatectomy. These animals showed better recovery of the remnant liver volume and the plasma disappearance rate of indocyanine green on POD7. In contrast, group B showed exacerbation of liver damage. Measurements of the serum OLP concentration showed that 10 ng/mL OLP was appropriate for a hepatoprotective effect. In conclusion, pretreatment with OLP shows hepatoprotective effects in a swine partial hepatectomy model. OLP may have the potential to ameliorate patients' outcomes after hepatectomy or liver transplantation. Liver Transpl 20:838–849, 2014. © 2014 AASLD.